Penerapan Zero Waste di Pemukiman Warga Sekitar Tempat Pembuangan Akhir Sampah di Kecamatan Puuwatu, Kendari - Uli Fermin; Rahayu Endah Purwanti; Laode Muhammad Harjoni Kilowasid; Waode Nuraida; Febri Dian Handayani; La Mudi (Institut Pertanian Bogor, 2020)
Waste is a source of problems, if not managed properly it will cause environmental pollution, especially in residential settlements that live around landfills in Puuwatu District. The purpose of this community service activity is to reduce the pile of waste in the Puuwatu sub-district landfill through the application of the principle of zero waste, namely by processing organic solid waste into compost, leachate into a decomposer microorganism solution, and recycling inorganic waste for verticulture media. Activities undertaken to achieve the objectives of the Community Partnership Program (PKM) are through mass and group counseling to partners, training and plot demonstrations. Through these activities, partners who live around the landfill had been able to process organic solid waste, with the hope that the volume at the landfill will decrease, and the partner's income will increase. Partners who were actively involved in the activity had been able to produce compost (labeled Komsa-Mitra) that was ready to be commercialized, and are also able to process leachate as a source of decomposer microorganisms (labeled mollin) in the composting process. Partners around the Puuwatu landfill were also able to utilize waste plastic and rubber containers into a vegetable cultivation container with a verticulture system in the yard and the hervested vegetable was used to meet the family's nutritional needs.